2001
DOI: 10.1016/s1441-3582(01)70175-9
|View full text |Cite
|
Sign up to set email alerts
|

Brand Extensions: Prestige Brand Effects

Abstract: Competition and consumer brand attitudes make introducing a new brand risky and very expensive, increasing the attractiveness of brand extensions. Brand extension research has established that original brand quality perceptions, product category fit, consumer perceptions of the product category complementarity and substitutability, plus the transferability of design and manufacturing capability significantly influence extension attitude formation. However, these studies fail to differentiate between brand type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 24 publications
1
35
0
1
Order By: Relevance
“…Brand prestige can influence consumers' brand purchase intention through enhancing their confidence during brand selection, and their social status and selfdom after brand purchase (Baek et al,2010). Brand prestige is a more salient concept than functional concepts (Lye et al,2001). It may be noteworthy for consumers because of its relation to their self-concepts (Keller,1998), wealth, power and social image (Alden et al,1999).…”
Section: Personality Congruencementioning
confidence: 99%
“…Brand prestige can influence consumers' brand purchase intention through enhancing their confidence during brand selection, and their social status and selfdom after brand purchase (Baek et al,2010). Brand prestige is a more salient concept than functional concepts (Lye et al,2001). It may be noteworthy for consumers because of its relation to their self-concepts (Keller,1998), wealth, power and social image (Alden et al,1999).…”
Section: Personality Congruencementioning
confidence: 99%
“…Only little research (e.g., Hagtvedt & Patrick, 2009;Monga & John, 2010) has been done on brand extensions for luxury brands so far. This is surprising because quite a few authors (e.g., Lye, Venkateswarlu, & Barrett, 2001;Monga & John, 2010;Völckner & Sattler, 2007) explicitly state that the insights gained from brand extension research in the nonluxury context cannot easily be transferred to the luxury context due to the different nature of luxury brands. For example, luxury brands (as opposed to nonluxury brands) are stronger on symbolic and experiential benefits (Vickers & Renand, 2003).…”
Section: Literature Review On Luxury and Nonluxury Brand Extension Rementioning
confidence: 99%
“…Park, Milberg, and Lawson (1991) have shown that prestige brands are more extendible if the brand concept is consistently transferred, even if product-feature similarity is low. To conceptualize prestige-oriented brand concepts, the authors mainly resort to dimensions related to the self-concept of the consumer (Lye, Venkateswarlu, & Barrett, 2001). Roux (1995) has identified conceptual fit and brand quality as the main determinants of perceived extension quality for luxury brands.…”
Section: Literature Review On Luxury and Nonluxury Brand Extension Rementioning
confidence: 99%
See 2 more Smart Citations